Anguilla bengalensis - Esmaeili, Hamid Reza; Hamidan, Neshat (Zenodo, 2023)
1. Anguilla bengalensis (Gray, 1831) ―Mottled Eel/ African or Indian Mottled Eel― Native Taxonomy. Original description: Muraena bengalensis Gray, 1831:no page number, Pl. 95 (fig. 5) [India; No types known]. Synonyms: Anguilla arracana McClelland, 1844; Anguilla brevirostris McClelland, 1844; Anguilla elphinstonei Sykes, 1839; Anguilla variegata McClelland, 1844. Status in the Arabian Peninsula. First report from the Arabian Peninsula by Attaala & Salim Rubaia (2005); confirmed by Freyhof et al . (2020:113), and Heemstra et al. (2022:84). General distribution and Habitat. Indian Ocean and adjacent freshwater habitats: South Africa north to Kenya, east to Malaysia, north to Nepal. Freshwater, brackish, marine. Distribution in the Arabian Peninsula. Recorded from Yemen in Wadis Hajr and Masila (Attaala & Salim Rubaia 2005; Freyhof et al. 2020). Economic importance. No commercial importance. Conservation. Near Threatened (NT). Remarks. It has been recognised as A. bengalensis labiata (East African populations) and A. bengalensis bengalensis (the Indian Ocean populations), (Heemstra et al. 2022: 83). Fricke et al. (2023) considered Anguilla labiata (Peters, 1852) as a distinct species. Published as part of Esmaeili, Hamid Reza & Hamidan, Neshat, 2023, Inland fishes of the Arabian Peninsula: Review and a revised checklist, pp. 201-226 in Zootaxa 5330 (2) on pages 205-206, DOI:10.11646/zootaxa.5330.2.2, http://zenodo.org/record/8249316